2021
DOI: 10.1002/ddr.21801
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin inhibited oxidative stress and apoptosis of high glucose‐induced podocytes by inhibiting STAT1 pathway

Abstract: Azithromycin (AZM) has a therapeutic effect on diabetes, but there is no report on whether AZM has a therapeutic effect on diabetic nephropathy (DN) and its specific mechanism. Cell survival was detected by CCK‐8. The expression of the inflammatory factors TNF‐α, IL‐1β, and IL‐6 was determined by ELISA. The expression of inflammatory proteins MCP‐1, NLPR3, and ASC was detected by western blot. The expression of MDA, LDH, and SOD was detected by the appropriate kit. Apoptosis was detected by flow cytometry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…However, when oxidative stress overpowers the redox balance, it leads to the proinflammatory environment, which plays an important role in neurovascular degeneration in retinal diseases. ,, Because of their defensive function, microglia have a very strong antioxidant system. Still, the oxidative stress becomes detrimental and leads to cell death in microglia. ,,, Interestingly, AZM could prevent the intracellular oxidative stress formation in glia which is corroborative with earlier findings, in which AZM exhibited antioxidant activity in the high glucose-induced podocyte . These antioxidant properties of AZM could be ensued by nuclear translocation of Nrf2 and hence increasing the expression of downstream antioxidant genes. , By virtue of the inhibition of oxidative stress, the AZM pretreatment could prevent the microglia from entering into the proinflammatory phase and inhibits the secretion of inflammatory cytokines such as IL-1β and TNF-α.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, when oxidative stress overpowers the redox balance, it leads to the proinflammatory environment, which plays an important role in neurovascular degeneration in retinal diseases. ,, Because of their defensive function, microglia have a very strong antioxidant system. Still, the oxidative stress becomes detrimental and leads to cell death in microglia. ,,, Interestingly, AZM could prevent the intracellular oxidative stress formation in glia which is corroborative with earlier findings, in which AZM exhibited antioxidant activity in the high glucose-induced podocyte . These antioxidant properties of AZM could be ensued by nuclear translocation of Nrf2 and hence increasing the expression of downstream antioxidant genes. , By virtue of the inhibition of oxidative stress, the AZM pretreatment could prevent the microglia from entering into the proinflammatory phase and inhibits the secretion of inflammatory cytokines such as IL-1β and TNF-α.…”
Section: Discussionsupporting
confidence: 83%
“… 15 , 17 , 40 , 41 Interestingly, AZM could prevent the intracellular oxidative stress formation in glia which is corroborative with earlier findings, in which AZM exhibited antioxidant activity in the high glucose-induced podocyte. 42 These antioxidant properties of AZM could be ensued by nuclear translocation of Nrf2 and hence increasing the expression of downstream antioxidant genes. 43 , 44 By virtue of the inhibition of oxidative stress, the AZM pretreatment could prevent the microglia from entering into the proinflammatory phase and inhibits the secretion of inflammatory cytokines such as IL-1β and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to confirm that some non-specific FDA-approved drugs augment our natural interferon response while inhibiting and disrupting NF-κB signaling, including our repurposed Kelleni's immunomodulatory COVID-19 protocol that was shown to restore homeostasis of the SARS-CoV-2 inhibited and/or dysregulated interferon response (Kelleni, 2020b(Kelleni, , 2021a as well as to inhibit the concomitant SARS-CoV-2-induced robust activation of the IL-6 amplifier including NF-κB signaling as an essential component (Smart et al 2020;Kelleni 2021b) which was also showed by Nilsson-Payant and colleagues to play a fundamental role in SARS-CoV-2 replication (Nilsson-Payant Benjamin et al 2021). Moreover, we suggest that azithromycin might also disrupt the NF-κB and signal transducer and activator of transcription-1 synergistic induction of inflammatory genes expression that could also play a role in the dysregulated COVID-19 immune response (Hiroi and Ohmori 2005;Xing and Liu 2021).…”
Section: Kelleni's Protocol Might Inhibit Sars-cov-2 Replicationmentioning
confidence: 93%
“…Consequently, it may be of therapeutic benefit in various inflammatory disorders and to prevent graft-versus-host disease in patients undergoing stem-cell transplantation [167][168][169]. Furthermore, azithromycin has a therapeutic effect on diabetes as it inhibits oxidative stress, inflammation and apoptosis [170]. It combats epithelial barrier dysfunctions [171,172] and promotes connective tissue remodeling [173].…”
Section: Use Of Immunomodulatory Antibioticsmentioning
confidence: 99%